Dual CD47 and PD‐L1 blockade elicits anti‐tumor immunity by intratumoral CD8+ T cells - Susan N Christo; Keely M McDonald; Thomas N Burn; Nadia Kurd; Jessica Stanfield; Megan M Kaneda; Ruth Seelige; Christopher P Dillon; Timothy S Fisher; Bas Baaten; Laura K Mackay (Clinical & Translational Immunology)
Abstract Objectives Bispecific antibodies targeting CD47 and PD‐L1 (CD47 × PD‐L1 BisAb) demonstrate efficacy against a range of solid cancers. While dual blockade negates anti‐CD47‐mediated toxicity, the effect of combined innate and adaptive immune activation on protective tumor‐resident CD8+ T cells has yet to be fully elucidated. Methods CD8+ T cell populations were tracked upon CD47 × PD‐L1 BisAb treatment in an orthotopic model of murine breast cancer where anti‐tumor immunity is mediated by CD8+ T cells. Immune responses were also compared with anti‐PD‐L1 monotherapy to assess the advantage of dual checkpoint targeting. Results We found that CD47 × PD‐L1 BisAb treatment augmented CD8+ T cell responses in tumors, which resulted in enhanced tumor control. Compared with anti‐PD‐L1 treatment, dual CD47 and PD‐L1 blockade promoted greater numbers of antigen‐specific tumor‐resident CD8+ T cells that exhibited increased cytokine production. Conclusions Engagement of innate and adaptive immune checkpoint molecules via CD47 × PD‐L1 BisAb treatment resulted in robust CD8+ T cell responses, including the induction of tumor‐resident CD8+ T cells that exhibited functionally superior anti‐tumor immunity. These results demonstrate that innate immune activation potentiates anti‐tumor adaptive responses, highlighting the use of dual checkpoint blockade as an optimal strategy for promoting CD8+ T cell‐mediated protection.